Matemática e cotidiano: saberes escolares e suas relações com os vivenciados na pesca artesanal em comunidades de pescadores e marisqueiras em São Cristóvão, SE - Silveira, Angela dos Santos (2022)
Mathematical knowledge consists of a human construction in the quest to meet their survival needs. Thinking about the ways in which this knowledge was built and transmitted/taught is a way of trying to break with the paradigm that mathematical knowledge is something “ready”, “finished” and to present Mathematics as a living science, as in fact it is. The present research aims to analyze possibilities and limitations for the insertion of Ethnomathematics for the contextualization of the teaching and learning process of Mathematics in the early years of Elementary School in schools of artisanal fishing communities in the municipality of São Cristóvão, SE. The study was based on a qualitative and quantitative approach with an ethnographic look and a theoretical contribution based on Ethnomathematics, since it sought to analyze the mathematical knowledge built/used by fishermen and shellfish gatherers in the art of fishing. To this end, three interconnected research actions were carried out: 1) a state-of-theart review with the objective of identifying, in academic productions based on Ethnomathematics, pedagogical practices, strategies and resources used in the teaching of Mathematics in traditional communities; 2) an investigation with 15 teachers from the early years of Elementary School in four schools in fishing communities in the municipality of São Cristóvão, SE: Colônia Miranda, Rita Cacete, Coqueiro and Pedreiras; and 3) interviews with eight fishermen/shellfish gatherers residing in these communities. This project was approved by the Ethics and Research Committee of the UFS, and its participants signed an informed consent form (ICF). Data analysis was performed using Discursive Textual Analysis (DTA). Among the results obtained, a diversity of productions addressing the theme was observed, with emphasis on the mathematical knowledge present in indigenous, African and quilombola cultures. Such knowledge refers to social practices, such as agriculture, making handicrafts and backpacks, building houses, producing and selling tortillas. However, few productions specifically related to artisanal fishing were found. The main mathematical knowledge identified in the art of fishing, built/used by fishermen and shellfish gatherers were those related to arithmetic operations (addition, subtraction, multiplication and division), basic notions of financial mathematics, applied mainly in the commercialization and attribution of the values of fish/ caught shellfish, as well as notions of measurement concepts (time, length, mass). The appropriation of this knowledge makes it possible for these professionals to carry out their daily tasks and move with some ease in the fishing activity. There were still few teaching strategies, which provide the approximation of school mathematical knowledge with those experienced in the daily lives of fishermen/shellfish communities. In this sense, teachers recognize the existence of mathematical knowledge present in these communities and that could be addressed in the classroom, but are not. It is concluded that it is necessary to (re)think the methodologies, strategies and teaching resources used in Mathematics classes in schools located in these communities so that the contextualization of this knowledge occurs, as well as the need for specific training for this directed curricular component for pedagogic teachers.